PELATIHAN PEMBUKUAN KEUANGAN SEDERHANA UNTUK DAPAT MENINGKATKAN KINERJA UMKM TIMBU DI DESA BOLO - Munandar, Aris; Safira, Fira; Novitasari, Putri; Nurilah, Diana (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
Bookkeeping training is carried out by conducting outreach and training to typical food business actors in the Timbul area. The main problem with regional specialty food businesses is that they do not have business records, so they cannot know for sure how much their business profits or losses are. The activity stages begin with observation and initial training preparation. The next stage is the implementation of activities starting from the opening, delivery of material, questions and answers, simulations and practice. The final stage is evaluating the results of the training activities as measured by the level of satisfaction of the training participants. The targets of the training activities are Timbu business actors, totaling 10 MSMEs. The result of the simple bookkeeping training is that Timbu business actors, who have rarely or even never carried out business records or bookkeeping, have been greatly helped by this training. Business actors can now carry out recording or bookkeeping using a simple method that is easy to understand. Apart from that, Timbu business actors have begun to realize the importance of recording or bookkeeping business transactions properly and properly for businesses on a micro, small, medium and large scale. Another benefit obtained by training participants is that Timbu business actors can find out the development of their business by separating personal finances from business finances. The simple bookkeeping training received a positive response and participants were very satisfied with the results of the training that had been carried out